The influence of family socioeconomic status on toothbrushing practices in Australian children. (7th October 2021) - Trinh, Van Anh; Tarbit, Emiri; Do, Loc; Ha, Diep; Tadakamadla, Santosh Kumar
Abstract: Objective: To assess the relationship between toothbrushing behavior and socio‐demographic characteristics in Australian children. Methods: Data were collected through the 2012–2014 Australian National Child Oral Health Survey (NCOHS). NCOHS was a cross‐sectional survey of representative school children aged 5–14 years of Australia with a total sample size of 24, 664 children. Results: Two‐thirds (69%) of Australian children brushed twice or more times a day and the mean age of starting toothbrushing with fluoridated toothpaste was 24 months. Males were less consistent with toothbrushing than females (OR = 0.85; 95% CI: 0.74–0.97) and the likelihood of brushing twice or more a day improved with the increase in age (OR = 1.05; 95% CI: 1.02–1.08). Children with university educated (OR = 1.80; 95% CI: 1.44–2.26), vocational trained parents'/guardians' (OR = 1.45, 95% CI 1.11–1.90), living in families with an income of >AU120, 000 (OR = 1.42; 95% CI: 1.08–1.89) and having an overseas born parent (OR = 1.30; 95% CI: 1.07–1.58) were more likely to brush their teeth twice or more a day than their comparative counterparts. Children in households with two children (OR = 1.33; 95% CI: 1.07–1.64) were more likely to brush twice or more than single‐child households. Children with a health welfare card tended to delay the start of toothbrushing by 1.4 months in comparison to those without a welfare card. Children with one of the caregivers born overseas started brushing later than those with Australia born caregivers ( B = 1.04; SE = 0.46). Children living in high income and educated families and households with two or more children tended to start toothbrushing at an earlier age. Conclusions: Several family socio‐demographic factors influenced toothbrushing habits in Australian children.